Detection of Newcastle disease virus of poultry by real time reverse transcription-polymerase chain reaction (Bangladesh Veterinarian, 2017)
A real-time reverse transcription - polymerase chain reaction (rRT-PCR) was used for the detection of Newcastle disease virus (NDV) of poultry. A panel of seven known isolates of NDV in the form of allantoic fluid, obtained from a laboratory repository, was used for the development of the test. RNA was extracted from the allantoic fluid with a magnetic processor based automated RNA extraction system. The identity of the reference virus was first reconfirmed by a conventional RT-PCR specific for the Fusion (F) protein gene. Using these RNA, the rRT-PCR protocol was optimized with regard to the reaction mix and thermal profile using published primers and probes specific for M gene. The sensitivity of standardized rRT-PCR was compared to that of the conventional RT-PCR using serial 10-fold dilutions of the RNA of a selected sample. The thermal profile was modified from the published one; the annealing and extension steps were combined to a single step performed at 60ºC. The adopted rRT-PCR successfully amplified M gene from all the seven reference samples with a CT value ranging from 15.28 to 32.68. The rRT-PCR for M gene was 100-fold more sensitive than the conventional RT-PCR for F gene. This is the first report of the use of rRT-PCR for the detection of NDV in Bangladesh. This test will be useful for virological surveillance, particularly for screening NDV in respiratory infections.Bangl. vet. 2016. Vol. 33, No. 1, 16-22